Clinical Signs and Pathology Associated With Domoic Acid Toxicosis in Southern Sea Otters (Enhydra lutris nereis) - Miller, Melissa A.; Moriarty, Megan E.; Duignan, Pádraig J.; Zabka, Tanja S.; Dodd, Erin; Batac, Francesca I.; Young, Colleen; Reed, Angelina; Harris, Michael D.; Greenwald, Katherine; Kudela, Raphael M.; Murray, Michael J.; et al. (Frontiers in Marine Science, 2021)
The marine biotoxin domoic acid (DA) is an analogue of the neurotransmitter glutamate that exerts potent excitatory activity in the brain, heart, and other tissues. Produced by the diatom Pseudo-nitzschia spp., DA accumulates in marine invertebrates, fish, and sediment. Southern sea otters (Enhydra lutris nereis) feed primarily on invertebrates, including crabs and bivalves that concentrate and slowly depurate DA. Due to their high prey consumption (25% of body weight/day), sea otters are commonly exposed to DA. Standardized necropsy, DA testing, and histopathology were used to identify DA-associated pathology in 700 southern sea otters examined from 1998 through 2018. Acute DA cases typically presented with central nervous system (CNS) clinical signs, lesions, and systemic vascular pathology; chronic cases presented with cardiovascular signs and pathology; and subacute cases exhibited either or both conditions. Acute DA toxicosis in southern sea otters was indicated by severe congestion and multifocal hemorrhage in the brain, cardiovascular system, and eyes. Subacute cases were characterized by CNS and cardiac lesion expansion accompanied by host response to DA-associated tissue damage. For chronic cases, cardiovascular pathology was often more severe than in the brain, but the lesions at both sites were relatively quiescent, reflecting previous damage. Acute, subacute, and chronic DA cases had the same lesion distribution. CNS pathology was common in the hippocampus, olfactory, entorhinal and parahippocampal cortex, periventricular neuropil, and ventricles. The circumventricular organs were also important DA targets; microscopic examination of the pituitary gland, other circumventricular organs, and eyes aided diagnosis of acute DA toxicosis in sea otters. DA-associated cardiac histopathology was common for cardiomyocytes and coronary arterioles. Cardiomyocyte loss and arteriosclerosis occurred in the same areas, suggesting a similar underlying mechanism. This is the first effort to develop a rigorous case definition for DA toxicosis in sea otters. Diagnosing this common but often occult condition is important for improving clinical care and assessing population-level impacts of DA in this federally listed threatened species. Because humans, sea otters, and other animals consume the same marine foods, efforts to characterize health effects of DA for southern sea otters can provide strong collateral benefits.